2016
DOI: 10.1093/nar/gkw162
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of the vlinc class of non-coding RNAs using systems biology approach

Abstract: Functionality of the non-coding transcripts encoded by the human genome is the coveted goal of the modern genomics research. While commonly relied on the classical methods of forward genetics, integration of different genomics datasets in a global Systems Biology fashion presents a more productive avenue of achieving this very complex aim. Here we report application of a Systems Biology-based approach to dissect functionality of a newly identified vast class of very long intergenic non-coding (vlinc) RNAs. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…Real targets of GLI1 would be expected to correlate with the GLI1 mRNA across a wide range of cell types, and the availability of a broad expression dataset across 833 human cell types and conditions generated by the FANTOM5 consortium allowed us to accomplish the testing of this assumption (Forrest et al, 2014). We calculated the Spearman correlation between the GLI1 mRNA and each target transcript as previously described (St Laurent et al, 2016). For PTCH1, HHIP, and PTCH2, the correlations were 0.47, 0.4, and 0.27, respectively.…”
Section: Identification Of Gli1 Target Genesmentioning
confidence: 99%
“…Real targets of GLI1 would be expected to correlate with the GLI1 mRNA across a wide range of cell types, and the availability of a broad expression dataset across 833 human cell types and conditions generated by the FANTOM5 consortium allowed us to accomplish the testing of this assumption (Forrest et al, 2014). We calculated the Spearman correlation between the GLI1 mRNA and each target transcript as previously described (St Laurent et al, 2016). For PTCH1, HHIP, and PTCH2, the correlations were 0.47, 0.4, and 0.27, respectively.…”
Section: Identification Of Gli1 Target Genesmentioning
confidence: 99%
“…Some lncRNAs are encoded between genes and are known as long intergenic noncoding RNAs (lincRNAs) 85 . Intergenic noncoding RNAs that are greater than 50 kB in length are known as very long intergenic RNAs (vlincRNAs) 86 .…”
Section: Long Noncoding Rna (Lncrnas)mentioning
confidence: 99%
“…Recent reports have described v ery long intergenic n on- c oding (vlinc)RNAs expressed in numerous human tissues [2123]. The vlincRNAs are RNA Pol II products that are nuclear, non-spliced, non-polyadenylated transcripts of >50 kb of contiguously expressed sequence that are not associated with protein coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…The vlincRNAs are RNA Pol II products that are nuclear, non-spliced, non-polyadenylated transcripts of >50 kb of contiguously expressed sequence that are not associated with protein coding genes. The initial reports annotated 2,147 human vlincRNAs from 833 samples in the FANTOM5 dataset [23, 24]. A more recent study identified an additional 574 vlincRNAs expressed in childhood acute lymphoblastic leukemia [25].…”
Section: Introductionmentioning
confidence: 99%